2016
DOI: 10.1111/jfd.12442
|View full text |Cite
|
Sign up to set email alerts
|

Temporary protection of rainbow trout gill epithelial cells from infection with viral haemorrhagic septicaemia virus IVb

Abstract: The branchial epithelium is not only a primary route of entry for viral pathogens, but is also a site of viral replication and subsequent shedding may also occur from the gill epithelium. This study investigated the potential of agents known to stimulate innate immunity to protect rainbow trout epithelial cells (RTgill-W1) from infection with VHSV IVb. RTgill-W1 cells were pretreated with poly I:C, FuGENE(®) HD + poly I:C, lipopolysaccharide (LPS), LPS + poly I:C or heat-killed VHSV IVb and then infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…The rainbow trout gill epithelial cell line RTgill-W1 (Bols et al, 1994) was used because our laboratory previously demonstrated that reduced viral haemorrhagic septicaemia virus (VHSV) IVb was present in this cell line after treatment with killed VHSV but that stimulation of many known anti-viral genes was not responsible (Al-Hussinee et al, 2016). As a prelude to understanding the potential role of autophagy in disease resistance, the purpose of this study was to expand the repertoire of rainbow trout Atg genes and their induction under nutrient restriction in vitro in RTgill-W1.…”
Section: Introductionmentioning
confidence: 99%
“…The rainbow trout gill epithelial cell line RTgill-W1 (Bols et al, 1994) was used because our laboratory previously demonstrated that reduced viral haemorrhagic septicaemia virus (VHSV) IVb was present in this cell line after treatment with killed VHSV but that stimulation of many known anti-viral genes was not responsible (Al-Hussinee et al, 2016). As a prelude to understanding the potential role of autophagy in disease resistance, the purpose of this study was to expand the repertoire of rainbow trout Atg genes and their induction under nutrient restriction in vitro in RTgill-W1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of the interaction between host and pathogen has led to the demonstration that variable outcomes occur even when similar research models are employed (Garcia‐Valtanen et al., 2014; Liu et al., 2015). Previously, the rainbow trout epithelial cell line RTgill‐W1 was shown to be susceptible to VHSV IVb infection (Pham et al., 2013), but pretreatment of the cells with heat‐inactivated VHSV IVb reduced virus replication without increased expression of antiviral cytokines (Al‐Hussinee et al., 2016). Therefore, we investigated the role of autophagy in the RTgill‐W1 during infection with VHSV IVb.…”
Section: Discussionmentioning
confidence: 99%
“…A one‐step RT‐qPCR was used to detect the VHSV IVb viral RNA copy number in the cellular RNA extraction (Al‐Hussinee et al., 2016). The LightCycler 480 RNA Master Hydrolysis Probes (Roche) Kit was applied in the LightCycler 480 Instrument II System (Roche) according to the instruction of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cell cultures such as the RTgill-W1 cell line developed from a primary culture of rainbow trout gill Oncorhynchus mykiss (Walbaum) ( 13 ) can be very useful to delineate specific molecular and cellular activation pathways. The RTgill-W1 cell line has been used to study the antiviral response ( 14 ), the effect of osmoregulatory hormones ( 15 ) and in ecotoxicological studies ( 16 ). In RTgill-W1 cells cultured under transwell conditions canonical features of normal epithelial function are observed such as pavement cells (PVCs) and microridges however are absent in flask culture.…”
Section: Introductionmentioning
confidence: 99%